Identification and monitoring of the state of illegal amber mining lands - Yanchuk, R.; Dmytriv, O.; Ostapchuk, S.; Prokopchuk, A.; Trokhymets, S.; Yanchuk, O. (Land Management, Cadastre and Land Monitoring, 2022)
The negative consequences of illegal amber mining in Ukraine are analyzed. Emphasis is placed on the urgent need for a reliable assessment of the extent of illegal mining, determining the area of such sites and the necessary amount of their further reclamation.As part of scientific and technical research commissioned by the Ministry of Education and Science of Ukraine "Development of a system for identification and monitoring of lands damaged by amber mining" in the northwestern part of Ukrainian Polissya selected 5 test plots of 100 km2 with the highest distribution of disturbed lands. The test areas have clear features and a significant area of merged contours.An integrated approach has been proposed for the identification and monitoring of such areas, which involves the use of multi-zone satellite images, mapping from unmanned aerial vehicles, and ground geodetic measurements. A methodology for such research has been developed. To automate the work on the basis of the free open source program QGIS 3.4.2, the structure was substantiated and a modular geographic information system was developed. Verification of the areas of disturbed lands on the basis of satellite survey materials and field geodetic measurements has been performed. Some results of researches of the sites of the broken earths in the Sarny area of the Rivne area which testify to efficiency of the offered technique are resulted.Key words: amber, disturbed lands, monitoring, satellite images, ground geodetic surveys.